Impact of solid-electrolyte interphase layer thickness on lithium-ion battery cell surface temperature - Andriunas, Ignas; Milojevic, Zoran; Wade, Neal; Das, Prodip K. (Journal of power sources, 2022)
The widely used non-destructive battery characterization techniques, such as voltage, capacity, and impedance measurements, often fail to fully characterise a discarded lithium-ion battery when reuse of spent battery is envisaged. Here we propose a tool that uses the surface temperature of a pouch cell to measure the thickness of the solid-electrolyte-interphase (SEI) layer, which is often attributed as one of the main causes of lithium-ion battery degradation at 0.1C–1C discharge rates in ambient conditions. A 2D multiphysics coupled electrochemical-thermal continuum model and a 3D thermal model have been developed to investigate the changes in the surface temperature of a lithium-ion pouch cell with varying SEI layer thicknesses. Present modelling results show that the cell surface temperature changes due to significant SEI layer heat generation at several discharge rates. Furthermore, the temperature change has also been subject to different cooling conditions and particle sizes. The present results provide a reference to making decisions on battery reuse by providing a correlation between the SEI layer thickness with the surface temperature of the cell and inform future research on thermal runaway as a thicker SEI layer can decrease the onset temperature of thermal runaway. •Battery temperature changes due to significant solid-electrolyte-interphase heat.•Anode particle size changed the thermal impact of the solid-electrolyte-interphase.•Thermal impact of the solid-electrolyte-interphase depends on depth-of-discharge.